2005
DOI: 10.1371/journal.pcbi.0020098.eor
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulations of cotranslational protein folding: fragment stabilities, folding cooperativity and trapping in the ribosome tunnel

Abstract: Although molecular simulation methods have yielded valuable insights into mechanistic aspects of protein refolding in vitro, they have up to now not been used to model the folding of proteins as they are actually synthesized by the ribosome. To address this issue, we report here simulation studies of three model proteins: chymotrypsin inhibitor 2 (CI2), barnase, and Semliki forest virus protein (SFVP), and directly compare their folding during ribosome-mediated synthesis with their refolding from random, denat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…The simulation results reported here can be reconciled with available experimental data, but their full validation will depend on forthcoming CF experiments. Future computer simulations will use more detailed coarse grained models, which will provide protein specific predictions 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation results reported here can be reconciled with available experimental data, but their full validation will depend on forthcoming CF experiments. Future computer simulations will use more detailed coarse grained models, which will provide protein specific predictions 14…”
Section: Discussionmentioning
confidence: 99%
“…This result was attributed to the fact that CF facilitates the assembly of local native structure that in turn steers folding away from the local energy minima, which act as RF kinetic traps. The computational study using Go off‐lattice models performed by Elcock14 compared the folding during ribosome‐mediated synthesis with refolding from random denatured conformations for several proteins, including chymotrypsin inhibitor 2 (CI2) and barnase. Those simulations suggested that both CI2 and barnase fold post‐translationally via a mechanism identical to that of RF.…”
Section: Introductionmentioning
confidence: 99%
“…Its dimensions [Ϸ80-Å long and 10-to 20-Å wide at its narrowest point (20)], together with its conservative global flexibility (21), suggests that complete NC folding can only take place once it has emerged from the tunnel (22).…”
mentioning
confidence: 99%
“…This can be understood as due to two reasons: the faster diffusion at this temperature helps the protein to avoid trapped conformations, and the larger thermal fluctuations help the protein to get out from the traps. The trapping at an atomistic ribosome tunnel and the alleviation of trapping by increased thermal fluctuations have been also observed for the chymotrypsin inhibitor 2 (CI2) protein in an early simulation study by Elcock 14 . Our results here for GB1 are consistent with that previous work.…”
Section: A Effect Of Tunnel Shape On Escape Processmentioning
confidence: 78%
“…The latter can be observed near the tunnel exit port where there is enough space to hold the structure. Simulations 14,15 and experiments [16][17][18] indicate that cotranslational folding starts inside the tunnel, with the structures ranging from a non-native compact conformation 16 and transient tertiary structures 15 to a small protein domain 17 . There are also considerations that the folding inside the ribosome tunnel is negligible leading to a focus only on the folding of nascent chains as they emerge from the tunnel, as shown in studies with stalled ribosome-bound nascent chain experiments 19,20 and simulations 21,22 .…”
Section: Introductionmentioning
confidence: 97%